School Committee Strategies to Improve the Quality of Primary School Learning - Novalia Nurlaela; Deti Rostini, (Journal of Science and Education (JSE), 2025)
This study examines the strategies employed by school committees to enhance the quality of learning at the primary school level within the context of the implementation of the Merdeka Curriculum. Using a qualitative case study approach, the research was conducted at SDN 170 Dian in Bandung City and SDN Menger 02 in Bandung Regency, involving principals, teachers, committee members, and parents. Data were collected through participatory observations, in-depth interviews, and document analysis, and were analyzed using the interactive model by Miles, Huberman, and Saldaña. The findings indicate that school committee strategies include data-driven planning, participatory program implementation, and monitoring through documentation and reporting. However, the committee’s involvement remains largely administrative and has not fully assumed a strategic role. This role gap is attributed to the committee’s limited human resource capacity, lack of training, and weak synergy among stakeholders. The study concludes that the effectiveness of school committee strategies in supporting learning quality hinges on three key factors: adaptive policy support, institutional capacity building, and the application of a community-based collaborative approach. These findings underscore the importance of transforming school committees from symbols of administrative participation into strategic actors in school-based quality education management.